Anthropometric and physical performance requirements to be selected in elite handball academies: is being left-handed an advantage? - Karcher, C.; Buchheit, M. (Sport Performance & Science Reports, 2017)
Playing handball requires players to repeat explosive actions such as sprints, jumps, changes of direction and throws at maximal intensity. Game demands are largely playing-positions dependent (1), which explains the large difference in technical, anthropometric (2) and physical performance pro le of players representative of each position (3, 4). For playing organization purposes and e cient ball circulation, there need to be at least 2 left-handed players on the court during matches. Since these players need to be substituted like any other players on the court, each team comprises in general at least 4 left-handed players. While this proportion represents 25% of a handball team, only 10% of the French population is left-handed (5).There is therefore a feeling that being left-handed may be an advantage with regard to selection, and that they may not need to be as tall, fat or explosive as their right-handed peers. However, this has yet to been examined. Aim. The aim of this study was to compare the maturity status, anthropometric pro le and physical performances of left vs. right-handed young players playing at the same position in an elite academy.